Annotations to be with the literature: Annotations to be with the literature - Madriz Boscán , Ángel Enrique (Encuentro Educacional, 2022)
Many times, reading is conceived as a strictly solitary, playful, hedonistic activity; and writing, a way of hiding from the world in order to express fearful speech and, for similar reasons, criticism is the response of someone who has not been able to write something similar to what he reads. The purpose of this essay was to explain about writing, reading and criticizing and its importance in literature. From the methodological point of view, a documentary, qualitative and interpretive research was carried out. Theoretically, the contributions of renowned authors were considered on how the role of the writer is inextricably linked to his historical performance as a reader, which is in turn an active experience of his condition as a social, individual being, that is, as a historical character full of emotions, feelings and with an intelligentsia with which it is possible to give pertinent answers to a society that has enriched him and of which he is always attentive to contribute to its transformation, because writing and reading demand his irrevocable critical contributions. In short, and not as a theoretical conclusion but as a cultural conviction, we simply cannot be writers if we have not been great readers before, because writing is definitely a continuity with the history we live in and, fortunately, we enrich it with our critical reflections.